Development Strategy for the Ciburuy Site as a Historical and Cultural Tourism Destination Bayongbong District, Garut Regency - Syah, Yoga Ramadhan; Adiatma, Dani; Dhamayanty, Stanny (Universitas Syiah Kuala, 2025)
This study aims to formulate a development strategy for the Kabuyutan Ciburuy Site as a sustainable historical and cultural tourism destination. The site is a Sundanese cultural heritage that holds significant historical, spiritual, and ecological value, yet faces various challenges in terms of preservation and management. The research employs a descriptive qualitative approach with data collection methods including observation, in-depth interviews, and literature studies. SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats that influence the sites development. The findings indicate that the Kabuyutan Ciburuy Site has great potential as an educational and spiritual tourism attraction, supported by ancient manuscripts, traditional buildings, and living local traditions. However, the deteriorating physical condition of some structures, limited basic facilities, and lack of government support present major challenges. The recommended strategies include cross-sector collaboration, the use of digital technology, strengthening the capacity of local managers, and safeguarding the sites sacred values. With integrated and participatory development, the site has the potential to become an icon of local cultural preservation as well as a driver of a local wisdom-based economy in Garut.